Intervenciones de enfermería en pacientes postquirúrgicos en nefrectomía radical: revisión sistemática - Mayancela Nivelo, Narcisa De Jesús (2025)
Introduction: Radical nephrectomy is that surgical process where one of the patient's kidneys is removed due to some type of chronic kidney disease that directly affects the patient's quality of life, so once performed the surgery requires physical care, but also psychosocial. Objective: To describe nursing interventions in post-surgical patients in radical nephrectomy, through a systematic review. Materials and methods: A systematic review was carried out with a qualitative modality, since the findings found are theoretically analysed, from the use of the PRISMA methodology to ensure the reliability and veracity of the information collected, bibliography from 2021 to 2024 was taken into consideration and in English, Spanish and Portuguese, for free use, obtained from databases such as Pudmed, Researchgate, Google Scholar, where 20 documents that met the inclusion criteria were identified. Results: Nursing interventions in post-surgical patients undergoing radical nephrectomy include pain management, early mobilization, infection control, and patient education on self-care. It was observed that a timely and personalized intervention significantly improves clinical results, reducing postoperative complications such as infections and thromboembolism, in addition to favouring a faster and safer recovery. Conclusion: Nursing interventions play a crucial role in the postoperative period of radical nephrectomy, being essential to their proper implementation to optimize the quality of life of patients and minimize post-surgical risks.